An Analysis of Illocutionary Acts in TED Talks 2024 on English Language Learning - Barokah, Anisa Utami; Areni, Galuh Kirana Dwi (Universitas Negeri Semarang, 2025)
In language learning, illocutionary acts is essential in shaping communicative competence. The research employs a descriptive qualitative approach to analyze the illocutionary acts in two 2024 TED Talks on English language learning using Searle’s (1976) classification as its analytical framework. The research aims to identify 5 illocutionary act types with the most dominant ones in selected videos and investigate the correct usage of illocutionary acts to better understand how language is used in educational discourse. The data were systematically classified into five distinct categories of speech acts: representatives, directives, expressives, commissives, and declaratives. The research identified that there were 159 illocutionary acts, consisting of 106 representatives (66.7%), 23 directives (14.5%), 19 expressives (11.9%), 11 commissives (6.9%), with no declarative acts identified in either video. The analysis reveals that the dominance of representative acts reflects the informative and persuasive goals of TED Talks, while directives, expressive, and commissive acts serve to enhance engagement, emotional resonance, and speaker credibility. These patterns show that effective educational discourse not only relies on vocabulary and grammar but also on strategically chosen illocutionary acts. This research suggests that to achieve communication goals, language users should not only concentrate on linguistic accuracy but also on employing illocutionary acts effectively to enhance their communication. Future research might extend this study by investigating larger and more diverse genres, different methodologies, or additional communicative dimensions. In conclusion, illocutionary acts are used strategically and contextually, shaped by the speaker’s purpose, background, and communication setting.